2021
DOI: 10.1073/pnas.2022960118
|View full text |Cite
|
Sign up to set email alerts
|

Prednisolone rescues Duchenne muscular dystrophy phenotypes in human pluripotent stem cell–derived skeletal muscle in vitro

Abstract: Duchenne muscular dystrophy (DMD) is a devastating genetic disease leading to degeneration of skeletal muscles and premature death. How dystrophin absence leads to muscle wasting remains unclear. Here, we describe an optimized protocol to differentiate human induced pluripotent stem cells (iPSC) to a late myogenic stage. This allows us to recapitulate classical DMD phenotypes (mislocalization of proteins of the dystrophin-associated glycoprotein complex, increased fusion, myofiber branching, force contraction … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 39 publications
(65 citation statements)
references
References 61 publications
(77 reference statements)
6
49
0
Order By: Relevance
“…Additionally, we found that transitional and mature myofibers frequently show fast motions as consequences of active contractions (Figure S6A, B and Movie S6). Similar active contractions have been observed when severing immature myofibrils in Drosophila, as a consequence of laser-induced calcium release from the sarcoplasmic reticulum [14] and have also been observed spontaneously in mature human myofibers after applying the same differentiation protocol [19]. This demonstrates that transitional myofibers harbour already contractile sarcomeres.…”
Section: Mechanical Tension Build-up Precedes Sarcomere Assemblysupporting
confidence: 74%
See 4 more Smart Citations
“…Additionally, we found that transitional and mature myofibers frequently show fast motions as consequences of active contractions (Figure S6A, B and Movie S6). Similar active contractions have been observed when severing immature myofibrils in Drosophila, as a consequence of laser-induced calcium release from the sarcoplasmic reticulum [14] and have also been observed spontaneously in mature human myofibers after applying the same differentiation protocol [19]. This demonstrates that transitional myofibers harbour already contractile sarcomeres.…”
Section: Mechanical Tension Build-up Precedes Sarcomere Assemblysupporting
confidence: 74%
“…We generated human iPSC-derived myogenic precursors by differentiating NCRM1 iPS cells for 20-30 days according to [18]. These cultures were then dissociated and filtered through a 70 µm and then a 40 µm cell filter to obtain singlecell suspensions, and replated in SKGM-2 medium for 1 to 2 days to generate cultures enriched in myogenic precursors prior to freezing [18,19]. Frozen myogenic precursors were then thawed, seeded on Matrigel-coated ibidi® glass-bottom dishes and grown in proliferation medium (SKGM-2) for 2-3 days before switching to KCTiP differentiation medium (see methods).…”
Section: Human Ipsc-derived Myofibers Follow a Biphasic Differentiation Processmentioning
confidence: 99%
See 3 more Smart Citations